Towards a new model to benchmark firms' operating efficiency: A data envelopment analysis approach. Issue 3 (2nd September 2017) - Oberholzer, Merwe; Mong, Dawie; van Romburgh, Jan
Abstract : The purpose of the study was to construct two similar data envelopment analysis (DEA) models. The first contains only published accounting-based data and the second added weighted average cost of capital (WACC), a primary market-based determinant, as an input variable. The efficiency scores of firms according to the two models are compared to determine whether there is a significant difference between the two models' results. In total, 206 company years were analysed. This includes all the manufacturing firms which published financial statements on the Johannesburg Security Exchange (JSE) from 2011 to 2013. The study found that there is a good chance that the efficiency score of a firm will be significantly lower when WACC is added as a variable. Therefore, ignoring WACC in a general benchmarking DEA model may provide a misleading, too optimistic, sugar-coated answer to firms' managers with regard to their firms' relative operating efficiency. The study contributes to the existing body of literature by revealing evidence that WACC is an important component in a DEA model that aims to benchmark firms' operating efficiency. Therefore, accounting-based data should be used in conjunction with WACC, a primary market-based determinant, which adds a further dimension to the benchmarking model.